W sprawie konieczności zachowania przedludzkich systemów komunikacyjnych (bezjęzykowych) w kontekście zachowania bioróżnorodności - Puppel, Stanisław (Studia Rossica Posnaniensia, 2021)
On the basis of the existing and unquestioned linguistic stance, a division of all the living creatures inhabiting the Earth into those which do not have language (i.e. prehuman and languageless) and those who have language (i.e. the genus Homo sapiens) is postulated. The paper briefly discusses a rich diversity of communication modes occurring in the domain of the prehuman communication systems, such as the auditory, visual, tactile, olfactory, electric, thermal, and seismic ones, with appropriate graphic illustrations. Furthermore, on the basis of the phenomenon of the observable shrinking of this diversity and the key position of the human species, it postulates the necessity of preserving this diversity in the context of biodiversity. This major postulate is in accord with the need to intensify attempts to preserve biodiversity as well as preserve the remaining diversity on the level of the prehuman communication systems as a major challenge of modern humanity. In this context, the human species is considered here as the species of the ‘overseers’ and ‘archivers’ of all the existing communication systems existing on the Earth as the carrier of the tree of life.